Exploring the Application of the Backward Design Model in EFL Classrooms: Teachers' Perceptions and Practices (Research, Society and Development, 2023)
This qualitative approach study aimed to explore and illustrate the teachers' perceptions in applying the Backward Design Model (BDM) in designing the Ecuadorian teaching syllabi for secondary public schools. Sixteen teachers were selected, and the data was gathered through the teachers' unit designs based on the BDM, teachers' reflections on the implementations of the BDM, and focus-group interviews. The analysis was done using a thematic approach. The researchers followed an interactive process by going forwards and backwards in reading, coding, and creating common themes that emerged from the collected data. The results indicate that the participants found the BDM planning a complex but fruitful process which allows them to better align the students' learning outcomes of each unit with the instructional materials, strategies, and teaching content based on a specific goal. The implications of this research lead to a possible consideration by the Ecuadorian Ministry of Education to enact this syllabus design according to the classroom context fully.